Cashew agroforestry and changing property rights in post-war Mozambique - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Mozambique was the world's number one producer of cashew nuts in shell in the 1970s. Cashew trees existed largely on smallholder land, in groves and intermixed with cassava, cowpea, maize, and groundnuts. A civil war beginning in the late 1960s and lasting nearly two decades changed the situation. The war dislocated people and stopped the planting and replacing of the old and unproductive cashew trees. Restoration of peace in the 1990s brought land tenure issues to the fore. Many demobilized and displaced smallholders returned to find their lands occupied by others, resulting in significant numbers of land disputes. Rural households expanded areas under cultivation as farmers brought areas long under fallow due to the war back into cultivation. There were also large-scale recovery efforts to rehabilitate agricultural sectors, such as cashew and livestock production.